Narasi Ekosemiotik Kultural dalam Novel Tanjung Kemarau Karya Royyan Julian: Resistensi Budaya dan Advokasi Lingkungan di Madura - Agik Nur Efendi; Anas Ahmadi; Titik Indarti; Magfirotul Hamdiah; Diah Kusyani; Wa Mirna; Siti Nurjanah; Rahma Anugraheny (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study examines the novel Tanjung Kemarau by Royyan Julian through an ecosemiotic perspective to explore cultural resistance and environmental advocacy in Madura Island. The primary focus of this research is how cultural symbols and narratives in the novel reflect the close relationship between the local community and the environment, particularly the mangrove forests. Using a descriptive qualitative approach, this study analyzes the symbolism and meanings related to ecological and cultural issues in the novel. The findings show that mangrove forests are not only viewed as physical ecosystems but also as sacred spaces revered by the community. Mystical figures such as Nyai Rasera and the village cleansing rituals are depicted as part of the community's efforts to preserve the environment and resist commercial exploitation. The novel serves as a form of resistance against environmentally destructive modernization practices, while also acting as an advocacy tool emphasizing the importance of preserving cultural values in ecological conservation. This research enriches the discourse of ecosemiotics in Indonesian literary studies and highlights the potential of literature as a medium for culturally-based environmental advocacy.